STRATEGI PEMBELAJARAN SASTRA BERBASIS LITERASI KRITIS DAN PENDIDIKAN KARAKTER - Hayon G. Nico (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2019)
Understanding (reading) the literature in this paper is intended to read literature in order to capture the author's intentions behind his impressive work; reading literature by understanding the contents and context of the narrative in literary texts (Priyatni, 2010) The content and context of literature is very complex because it is packaged in a complex code system, namely language codes, social codes, cultural codes, and literary codes (Teeuw, 1988). To understand literary texts with critical thinking, readers should have knowledge and understanding of these codes. The reader does not merely understand the language codes at the grammatical level, but more than that understands cultural codes as product and literary codes.